Transplantation and mutation in Anglo-American trust law - Getzler, J (De Gruyter, 2009)
In the early nineteenth century, authoritative treatise writers such as James Kent and Joseph Story represented Anglo-American trust law as a seamless web. But the transplantation of trust law from England to America was not a simple process of adherence. Rather, American courts and legislatures came to discard fundamental English trust doctrines. Restraints on anticipation and on alienation were embraced, and in key state jurisdictions bare trusts were abolished, or else displaced from the core of trust law. Irreducible settlor power over beneficiaries and the strong protection of beneficiaries from creditors under spendthrift trusts were two strikingly original American creations, which flowed from these basic doctrinal choices. The changes made to American trust doctrine yield a paradox for the legal, social and economic historian, namely that republican America ended up with a more dynastic property law, more wedded to dead hand control and more hostile to commercial creditors, than did aristocratic England with its unreformed system of common law and equity rooted in the feudal property system. The American abandonment of free alienability of beneficial interests and the corresponding reduction of the beneficiary's powers over trust assets may have been rooted in the volatility of credit in America and the desire of the wealthy to escape from the pressures of the market, though disparities between jurisdictions remain to be explained.